Tregs and transplantation tolerance - Walsh, Patrick T. (American Society for Clinical Investigation, 2004)
The induction and maintenance of immune tolerance to transplanted tissues constitute an active process involving multiple mechanisms that work cooperatively to prevent graft rejection. These mechanisms are similar to inherent tolerance toward self antigens and have a requirement for active immunoregulation, largely T cell mediated, that promotes specific unresponsiveness to donor alloantigens. This review outlines our current understanding of the Treg subsets that contribute to allotolerance and the mechanisms by which these cells exert their effects as well as their potential for therapy.